Social-Level Factors Related to Positive Mental Health Outcomes Following Intimate Partner Violence: Results from a Population-Based Aotearoa New Zealand Sample - Pir, Setayesh (Violence against women, 2022)
Intimate partner violence (IPV) continues to be an issue for women globally. There remains a gap in research about what contributes to better mental health following IPV. The sociodemographic characteristics and other factors associated with positive mental health were explored among a sample of 454 women aged 16 years and over who reported previous exposure to physical and/or sexual IPV. Sixty-six percent of women reported positive mental health. The cessation of violence, support at disclosure, and ongoing informal support were factors significantly associated with positive mental health. Greater community outreach to improve responses to disclosure and practical support is needed.